The 2024 Election as a Medium of Da'wah and Conceptual and Ideological Political Communication - Ahmad Burhan Hakim; Satryo Pringgo Sejati (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The general election or election is one of the important and historic moments that many people are waiting for. It is even sometimes in the spotlight of the international world. In 2024, Indonesia has successfully held direct elections. So it can be said that Indonesia is a Muslim country in the world that is able to implement modern democratic values or systems. In fact, elections are an important part of the democratization process in Indonesia. So this moment becomes a medium for da'wah and political communication both conceptually and ideologically. That in the election there will be a communication process both directly and indirectly from the candidates to be able to attract the sympathy of the people. Thus the flow of communication runs carefully. This means that in the democratic process, a model of da'wah or political communication emerges that will be consciously or not accepted by the community. Thus, the public will know how ideological the candidates are to be able to meet the expectations of the community. The research method used is a descriptive qualitative research method, using the approach of political science and da'wah science. Political da'wah is an important part that cannot be let go in elections. Political da'wah becomes a barometer and persuasive communication to get sympathy from the people and this is what then becomes very important in the election process. So that in the process, the Prabowo-Gibran pair was finally able to win the presidential election directly in 2024.